2018
DOI: 10.1111/jre.12556
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 3 calcium channel blockers on gingival overgrowth in a population of severe refractory hypertensive patients

Abstract: Nifedipine and amlodipine, but not felodipine, were associated with gingival overgrowth in patients with severe refractory hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…Karnik et al (2012) found the prevalence of amlodipine-induced DIGO to be 5.09%. However, Vidal et al (2018) found a higher prevalence with 45.4%. The prevalence among amlodipine users was 31.8% in our study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Karnik et al (2012) found the prevalence of amlodipine-induced DIGO to be 5.09%. However, Vidal et al (2018) found a higher prevalence with 45.4%. The prevalence among amlodipine users was 31.8% in our study.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, CCBs act on the calcium metabolism in cells, and since metalloproteinases involved in collagen breakdown in the matrix are regulated by calcium flow, fibroblasts cannot reduce active collagenases in patients who receive treatment with these drugs, which are responsible for the increase in extracellular matrix (ECM) (Dongari-Bagtzoglou, 2004). Several studies in the literature have reported that amlodipine may cause the development of DIGO (Karnik et al, 2012;Vidal et al, 2018). In approximately 50% of patients using CCBs after surgical treatment, gingival overgrowth has been demonstrated to recur despite receiving supportive periodontal therapy (Fardal & Lygre, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Interdental papillae are usually the initiation and most severe sites for DIGE. [ 2 3 ] Resolution of DIGE in the interproximal region after periodontal treatment may facilitate repristination of the transseptal fibers and direct the teeth to their original positions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may develop gingival enlargement (GE) after taking specific drugs, such as calcium channel blockers. [ 1 2 ] Strong evidence has indicated that poor oral hygiene exacerbates drug-induced GE (DIGE). [ 3 ] Furthermore, diabetes mellitus (DM) has been reported to affect GE although the underlying mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…La Cs es un inmunosupresor del sistema inmune, se indica para la prevención del rechazo de un órgano trasplantado o enfermedades autoinmunes y puede inhibir algu-nas de las funciones de los linfocitos T como el reconocimiento de antígenos, el procesamiento antigénico por macrógafos o la producción y liberación de interleuquina 1 (4) . El nifedipino es un bloqueador de los canales de calcio indicado para la hipertensión arterial y la angina de pecho (5) . Ambos medicamentos producen AG como efecto adverso.…”
Section: Introductionunclassified